Recent Developments in Bioprocessing of Recombinant Proteins: Expression Hosts and Process Development - Tripathi, Nagesh K.; Shrivastava, Ambuj (Frontiers in Bioengineering and Biotechnology, 2019)
Infectious diseases alongwith cancers are major cause of death in humankind across the world. Production of therapeutic proteins at large scale for millions of individuals to treat diseases is one of the essential needs of mankind. Recent progress in the area of recombinant DNA technologies has paved the way to produce recombinant proteins which can be used as therapeutics, vaccines and diagnostic reagents. Recombinant proteins for these applications are mainly produced using prokaryotic and eukaryotic expression host systems such as mammalian cells, bacteria, yeast, insect cells and transgenic plants at laboratory scale as well as large scale settings. Development of efficient bioprocessing strategies is crucial for the industrial production of recombinant proteins of therapeutic and prophylactic importance. Recently, advances have been made in the various areas of bioprocessing and are being utilized to develop an effective process for recombinant proteins. These include the use of high-throughput devices for effective bioprocess optimization, the use of disposable systems, continuous upstream processing, continuous chromatography, integrated continuous bioprocessing, use of Quality by Design, and process analytical technologies to achieve quality product with higher yield. This review summarizes the recent developments in bioprocessing of recombinant proteins which includes various expression systems, bioprocess development and recent advancement in upstream and downstream processing of recombinant proteins.